Uso e conservação de plantas medicinais nativas por comunidades quilombolas no município de Alcântara, Maranhão - Linhares, Jairo Fernando Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The municipality of Alcântara-MA was an important agricultural region in colonial times. After the decline of export agriculture, quilombos were recorded. The overall objective of the research is to rescue the knowledge of the Maroons in the municipality of Alcântara in Maranhão State, about medicinal plants, contributing to the conservation of quilombo territories, to guarantee the local knowledge and sustainable use of local biodiversity. Specifically, it seeks to: 1) Rescue and systematize knowledge of quilombo communities about medicinal plants. 2) Identify the botanically collected plants. 3) Identify past and current uses of medicinal plants. 4) Generate information to assist in the implementation of future management plans. 5) Assess the environmental, cultural and social changes. Of the 55 medicinal plants used at present, 58% are in disuse phase. The plants most commonly used today are Himatanthus drasticus (Mart.) Plumel), Cecropia sp., Hymenaea L., Parahancornia sp. Croton urucurana Baill., Myracrodruon urundeuva Allemão and Bauhinia glabra Jacq. The most plant parts were used: bark, 34 (27.42%) and latex, with 43 (35%), which together account for 62.42% of the plant parts used. Secondary forests are the main type of occurrence medicinal plants, with a history of agricultural use ranging from 15-30 years of fallow, medium CAP 29.27 cm, average height of 7.6 m, 69.76% of individuals is young trees and palm trees are the main growth habits with 65.41% and 26.86% each. Environmental tensioners that most compromise forest ecosystems today are the plantation system in play, lack of firebreaks in the formation of clearings, wood indiscriminate extraction, charcoal production, replacement of native pasture by cultivated in the areas of low and the consequent installment, practice of vandalism, variation in rainfall causing an increase in salinity in areas of shallow water during periods of ...

O município de Alcântara-MA foi uma importante região agrícola na época colonial. Após o declínio da agricultura de exportação, foram constituídos os quilombos. O objetivo geral da pesquisa é o de resgatar o conhecimento dos quilombolas do município de Alcântara no Estado Maranhão, acerca das plantas medicinais, contribuindo para a conservação dos territórios quilombolas, para a garantia do saber local e uso sustentável da biodiversidade regional. Mais especificamente, busca-se: 1) Resgatar e sistematizar o conhecimento de comunidades quilombolas sobre as plantas medicinais. 2) Identificar botanicamente as plantas coletadas. 3) Identificar usos passados e atuais das plantas medicinais. 4) Gerar informações que contribuam para a implementação de futuros planos de manejo. 5) Avaliar as mudanças ambientais, culturais e sociais ocorridas. Das 55 espécies medicinais usadas na atualidade, 58% estão em fase de desuso. As plantas mais usadas na atualidade são Himatanthus drasticus (Mart.) Plumel), Cecropia sp., Hymenaea courbaril L., Parahancornia sp. Croton urucurana Baill., Myracrodruon urundeuva Allemão e Bauhinia glabra Jacq. As partes vegetais mais usadas foram: casca, com 34 (27,42%) e o látex, com 43 (35%), que juntas representam 62,42% das partes vegetais mais usadas. As matas secundárias são a principal tipologia de ocorrência das plantas medicinais, com histórico de uso agrícola variando de 15-30 anos de pousio, CAP médio de 29,27 cm, altura média de 7,6 m, 69,76% dos indivíduos é jovem, as árvores e palmeiras são os principais hábitos de crescimento com 65,41% e 26,86%, cada. Os tensores ambientais que mais comprometem os ecossistemas florestais na atualidade são o sistema de roça no toco, falta de aceiros na formação dos roçados, extração indiscriminada de madeira, produção de carvão, substituição de pastagem nativa por cultivada nas áreas de baixa ...
Use and medical plant conservation in native quilombolas communities in Alcântara municipality, Maranhão
Keywords: Plantas medicinais - Brasil; Plantas medicinais - Conservação; Etnobotânica; Quilombolas; Medicinal plants